Game Online dan Prestasi Akademik Remaja Antara Motivasi dan Distraksi - Shobih, M . (Maliki Interdisciplinary Journal, 2025)
The digital era has significantly transformed the entertainment landscape for Indonesian adolescents, with online gaming emerging as a dominant activity. This phenomenon presents a dual-edged issue: while online games can enhance learning motivation through gamification and foster cognitive and social skills, excessive use poses risks to academic performance, concentration, and sleep quality. This study provides a comprehensive analysis of the dual impact of online gaming on the academic achievement of Indonesian teenagers, using a descriptive-analytical approach based on empirical data and recent literature. The findings suggest that the influence of online games is shaped by key factors such as playing duration, game type, students’ time management skills, and the support provided by families and schools. The article also explores strategies to optimize the educational potential of online games, including gamified learning integration, digital literacy reinforcement for parents and educators, and the development of balanced educational technology policies. The study concludes that a moderate and controlled approach to online gaming can offer new opportunities for educational innovation aligned with 21st-century challenges. ngan abad ke-21.